Manfaat Konsumsi Buah Nanas (Ananas comocus) terhadap Penurunan Plak Indeks pada Remaja - Koch, Novarita Mariana; Yuliana, Ni Made; Rondo, Usla Mika (Poltekkes Kemenkes Bandung, 2025)
Everyone desires to maintain good health, including adolescents. During adolescence, the consumption of foods high in sugar and simple carbohydrates tends to increase, which in turn increases the risk of plaque accumulation and dental and oral health problems. Promotive and preventive efforts through a healthy lifestyle, including fruit consumption, are needed to help reduce the plaque index, an indicator of dental health. The use of pineapple (Ananas comosus), which contains the enzyme bromelain and has natural cleansing properties, has the potential to play a role in maintaining dental and oral hygiene in adolescents. This study aimed to evaluate the effect of pineapple on the plaque index. The study was categorized as an analytical survey with a quasi-experimental approach. This was conducted with a one-group following pre and post tests, namely a study by comparing the conditions before and after treatment. Thirty respondents with 12-17 years old were involved. Sampling was obtained through total sampling. The study was conducted in Wioi Village, Ratahan Timur District, Southeast Minahasa Regency, North Sulawesi Province. Data analysis used the Wilcoxon test to determine the effect of pineapple consumption. The findings indicate that before treatment, the highest plaque index was in the Moderate category, with 19 people (63%). After treatment, there was a change in the majority of respondents with a Good category, with 25 people (83%). The Wilcoxon test demonstrated a statistically significant difference in the plaque index before and after pineapple consumption (p= 0.000). It concluded that pineapple consumption affects reducing the plaque index.